2020
DOI: 10.1007/s12539-020-00358-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA Mismatch Repair Deficiency Detection in Colorectal Cancer by a New Microsatellite Instability Analysis System

Abstract: Background Although microsatellite instability (MSI) is most commonly detected in colorectal cancer (CRC), improvement in MSI analysis method can always help us better assessing MSI phenotypes and gaining useful information in challenging cases. The purpose of current study is to explore whether the ProDx® MSI analysis System (ProDx® MSI) can improve MSI classification in CRC. Methods We compared the MSI profiles of 97 FFPE samples from CRC patients by ProDx® MSI with Promega MSI analysis System 1.2 and NCI pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Emerging PCR-based assays differ from the standard reference PCR method by the nature and number of targeted MS markers and/or the read-out strategy of PCR products ( Table 2 ). For example, some groups integrated the analysis of novel long mononucleotide repeats (LMR) besides the traditional pentaplex panel [ 58 , 59 ]. Bacher et al identified a large number of mononucleotide repeats with increased repeat length (40–60 bp) compared to the MS markers traditionally used for MSI testing [ 59 ].…”
Section: Other Msi Approaches On Tumour Tissue Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging PCR-based assays differ from the standard reference PCR method by the nature and number of targeted MS markers and/or the read-out strategy of PCR products ( Table 2 ). For example, some groups integrated the analysis of novel long mononucleotide repeats (LMR) besides the traditional pentaplex panel [ 58 , 59 ]. Bacher et al identified a large number of mononucleotide repeats with increased repeat length (40–60 bp) compared to the MS markers traditionally used for MSI testing [ 59 ].…”
Section: Other Msi Approaches On Tumour Tissue Samplesmentioning
confidence: 99%
“…Thus, the analysis of LMR markers allowed to enhance the detection sensitivity of the MSI-PCR assay. The commercial LMR MSI analysis system (Promega ® , Madison, WI, USA) that includes four conventional mononucleotide MS markers ( BAT25 , BAT26 , Mono27 , NR21 , and NR24 ) and 4 LMR markers ( BAT-52 , BAT-56 , BAT-59 and BAT-60 ) notably reached a higher agreement with IHC in colorectal samples compared to the Promega ® MSI analysis system [ 58 ]. The utility of such panel still needs to be confirmed for non-colorectal specimens.…”
Section: Other Msi Approaches On Tumour Tissue Samplesmentioning
confidence: 99%
“…Low or loss of MLH1 and PMS2 protein expression might often occur in TNBC patients based on our results and the published data available. Low-expressed PMS2 protein was also observed in one out of 10 cases of colorectal cancer in our previous study cohort, and other MMR proteins were all highly expressed in all samples (data not shown) ( 26 ). The potential biological implications of this process remain to be explored further.…”
Section: Discussionmentioning
confidence: 69%
“…The sample was considered to be microsatellite unstable if there was a shift of three base pairs in the tumor allele compared with normal tissue. MSI-H, MSI-L (low-frequency microsatellite instability), and MSS were distinguished when two or more, one, and no unstable markers were observed, respectively ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Primers were designed for mouse microsatellite loci L24372-A27, U12235-A24, mBat30, mBat37, mBat64, and mBat67 on mouse build GRCm38.p6 [37][38][39][40][41][42]. All primers were ordered as stated in Table S2 (Integrated DNA Technologies, Coralville, IA, USA) and amplified with Platinum™ SuperFi™ PCR Master Mix (12.5 µL; Thermo Fisher Scientific, Waltham, MA, USA) with kit-provided GC Enhancer (5 µL), with the exception of mBat67, where molecular grade water (5 µL) was substituted in place of GC Enhancer.…”
Section: Fragment Analysis and Sanger Sequencing To Assess Microsatel...mentioning
confidence: 99%